Welfare Consequences of Omitting Beak Trimming in Barn Layers - Riber, Anja B.; Hinrichsen, Lena K. (Frontiers in Veterinary Science, 2017)
Beak trimming is used worldwide as a method of reducing the damage to feathers and skin caused by injurious pecking in laying hens. However, beak trimming also causes some welfare issues as trimming the beak results in pain and sensory loss. Due to this dilemma, there is an on-going discussion in several European countries about whether to ban beak trimming. In the present study, we investigated the welfare consequences of keeping layers with intact beaks and examined for links between injurious pecking damage and keel bone damage on an individual level. A study was conducted on 10 commercial farms housing laying hens in the barn system. Each farm participated with a flock of beak-trimmed hens (T) and a flock of non-trimmed hens (NT) that were visited around 32 and 62 weeks of age. During visits, the condition of plumage, skin, feet and keel bone of 100 hens was assessed. Mortality was recorded by the producers. NT flocks had a lower prevalence of hens with good plumage condition around 32 weeks of age (94.1% v. 99.6%, P < 0.001) and a higher prevalence of hens with poor plumage condition at 62 weeks of age (63.6% v. 15.2%, P < 0.001) compared to T flocks. The prevalence of hens with keel bone deviations, with both keel bone fractures and deviations and with body wounds was higher in NT flocks compared to T flocks at both ages (P < 0.001). Accumulated mortality from placement to end of production tended to be higher in NT flocks compared to T flocks (14.2% v. 8.6%; P = 0.06). The prevalence of keel bone damage was higher among hens with poor plumage condition than hens with moderate/good plumage condition (31.5% v. 22.2%; P < 0.001). Thus, omitting beak trimming had negative consequences for the condition of plumage, skin and keel bone, and tended to increase mortality, highlighting the risk of reduced welfare when keeping layers with intact beaks. In addition, injurious pecking damage was found to be positively linked to keel bone damage. The causal relation is unknown, but we propose that fearfulness is an important factor.